Is Albumin Predictor of Mortality in COVID-19? - Violi, Francesco; Cangemi, Roberto; Romiti, Giulio Francesco; Ceccarelli, Giancarlo; Oliva, Alessandra; Alessandri, Francesco; Pirro, Matteo; Pignatelli, Pasquale; Lichtner, Miriam; Carraro, Anna; Cipollone, Francesco; D'ardes, Damiano; et al. (Antioxidants & redox signaling, 2021)
Coronavirus 2019 (COVID-19) is a pandemic associated with a high risk of mortality. Human serum albumin (HSA) is an acute phase reactant with antioxidant property; however, its behavior and impact on survival in COVID-19 patients have never been studied so far. Among 319 COVID-19 patients followed up for a median of 19 days, 64 died. Compared with survivors, nonsurvivors had more prevalence of intensive care unit (ICU) admission, chronic obstructive pulmonary disease (COPD), heart failure, elevated levels of D-dimer, high-sensitivity C reactive protein (hs-CRP) and troponins, and lower values of albumin. At the Cox regression analysis, albumin (hazard ratio [HR]: 0.38, 95% confidence interval [CI]: 0.23-0.63, p < 0.001) and age (HR: 1.03, 95% CI: 1.01-1.06, p = 0.001) were independently associated with mortality, irrespective of adjustment for gender, ICU admission, heart failure, COPD, and hs-CRP levels. Our observation leads to the hypothesis that HSA analysis may be used to identify patients at higher risk of death in COVID-19 patients.Coronavirus 2019 (COVID-19) is a pandemic associated with a high risk of mortality. Human serum albumin (HSA) is an acute phase reactant with antioxidant property; however, its behavior and impact on survival in COVID-19 patients have never been studied so far. Among 319 COVID-19 patients followed up for a median of 19 days, 64 died. Compared with survivors, nonsurvivors had more prevalence of intensive care unit (ICU) admission, chronic obstructive pulmonary disease (COPD), heart failure, elevated levels of D-dimer, high-sensitivity C reactive protein (hs-CRP) and troponins, and lower values of albumin. At the Cox regression analysis, albumin (hazard ratio [HR]: 0.38, 95% confidence interval [CI]: 0.23-0.63, p < 0.001) and age (HR: 1.03, 95% CI: 1.01-1.06, p = 0.001) were independently associated with mortality, irrespective of adjustment for gender, ICU admission, heart failure, COPD, and hs-CRP levels. Our observation leads to the hypothesis that HSA analysis may be used to identify patients at higher risk of death in COVID-19 patients.